2022
DOI: 10.1108/bij-06-2021-0341
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating logistics outsourcing: a survey conducted with Brazilian industries

Abstract: PurposeThis research aims to evaluate the factors that influence logistics outsourcing, including the impact of logistics outsourcing on measuring companies' logistics performance. This research provides interactions among the various factors (constructs) such as “financial”, “collaboration and process characteristics”, “external influencer”, and “logistics performance”.Design/methodology/approachTo investigate the interaction between the constructs, structural equation modelling is proposed to understand what… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 70 publications
(324 reference statements)
0
2
0
Order By: Relevance
“…RBV has been used in the literature currently available for logistics study. (Cho and Lee, 2020;Doratiotto et al, 2023;Dovbischuk, 2022;Elliot et al, 2020;Filho and Moori, 2020;Khan et al, 2022;König et al, 2019;Lukovszki et al, 2020;Lv et al, 2021;Nur' Atikah Zulkiffli et al, 2019;Pengman et al, 2022;Sazzadur Rahman Khan and Rattanawiboonsom, 2020). Cho and Lee (2020), utilizing RBV, transaction cost analysis (TCA), and institutional theory, examine how the increase in transportation would affect logistics.…”
Section: Literature Review Resource-based View Theorymentioning
confidence: 99%
See 1 more Smart Citation
“…RBV has been used in the literature currently available for logistics study. (Cho and Lee, 2020;Doratiotto et al, 2023;Dovbischuk, 2022;Elliot et al, 2020;Filho and Moori, 2020;Khan et al, 2022;König et al, 2019;Lukovszki et al, 2020;Lv et al, 2021;Nur' Atikah Zulkiffli et al, 2019;Pengman et al, 2022;Sazzadur Rahman Khan and Rattanawiboonsom, 2020). Cho and Lee (2020), utilizing RBV, transaction cost analysis (TCA), and institutional theory, examine how the increase in transportation would affect logistics.…”
Section: Literature Review Resource-based View Theorymentioning
confidence: 99%
“…Cho and Lee (2020), utilizing RBV, transaction cost analysis (TCA), and institutional theory, examine how the increase in transportation would affect logistics. Doratiotto et al (2023) Assess the factors that affect logistics outsourcing, including the impact of logistics outsourcing on the company's logistics performance measurement. Dovbischuk (2022) Investigated enterprise performance among logistics service providers during the coronavirus.…”
Section: Literature Review Resource-based View Theorymentioning
confidence: 99%
“…3PLs are characterised as IJPPM 73,1 contemporary supply chain orchestrators that establish and maintain a competitive edge for their customers. Doratiotto et al (2022) surveyed 129 Brazilian 3PL businesses as part of their study on logistics outsourcing. Collaboration and process factors have the greatest influence on 3PL logistics success, according to the study.…”
Section: Literature Reviewmentioning
confidence: 99%
“…3PLs are characterised as contemporary supply chain orchestrators that establish and maintain a competitive edge for their customers. Doratiotto et al. (2022) surveyed 129 Brazilian 3PL businesses as part of their study on logistics outsourcing.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Ref. [16] assessed the impact of logistics outsourcing on businesses' logistical performance and concluded that "collaboration and process characteristics" was the factor most strongly influencing logistics performance.…”
Section: Introductionmentioning
confidence: 99%